Energy-saving and emission-abatement potential of Chinese coal-fired power enterprise: A non-parametric analysis - Chu Wei; Andreas Löschel; Bing Liu (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2015)
In the context of soaring demand for electricity, mitigating and controlling greenhouse gas emissions is a great challenge for China's power sector. Increasing attention has been placed on the evaluation of energy efficiency and CO2 abatement potential in the power sector. However, studies at the micro-level are relatively rare due to serious data limitations. This study uses the 2004 and 2008 Census data of Zhejiang province to construct a non-parametric frontier in order to assess the abatement space of energy and associated CO2 emission from China's coal-fired power enterprises. A Weighted Russell Directional Distance Function (WRDDF) is applied to construct an energy-saving potential index and a CO2 emission-abatement potential index. Both indicators depict the inefficiency level in terms of energy utilization and CO2 emissions of electric power plants. Our results show a substantial variation of energy-saving potential and CO2 abatement potential among enterprises. We find that large power enterprises are less efficient in 2004, but become more efficient than smaller enterprises in 2008. State-owned enterprises (SOE) are not significantly different in 2008 from 2004, but perform better than their non-SOE counterparts in 2008. This change in performance for large enterprises and SOE might be driven by the "top-1000 Enterprise Energy Conservation Action" that was implemented in 2006.
Keywords: 330; Energy-saving potential; CO2 abatement potential; Weighted Russell Directional Distance Function; Coal-fired power enterprise